Enterprise systems and technological convergence : research and practice - Goundar, Sam, 1967- (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
Enterprise Systems have been used for many years to integrate technology with the management of an organization but rapid technological disruptions are now creating new challenges and opportunities that require urgent consideration. This book reappraises the implementation and management of Enterprise Systems in the digital age and investigates the vital link between business processes, information technology and the Internet for an organization's competitive advantage and success.This book primarily focuses on the implementation, operation, management and integration of Enterprise Systems with fastemerging disruptive technologies such as blockchains, big data, cryptocurrencies, artificial intelligence, cloud computing, data mining and data analytics. These disruptive technologies are now becoming mainstream and the book proposes several innovations that organizations need to adopt to remain competitive within this rapidly changing landscape. In addition, it examines Enterprise Systems, their components, architecture, and applications and enlightens readers on the benefits and shortcomings of implementing them.This book contains primary research on organizations, case studies, and benchmarks ERP implementation against international best practice.
Keywords: Business enterprises -- Computer networks.; Convergence (Telecommunication); Business -- Data processing.; Disruptive technologies.; Business & Economics -- Business Communication -- General.; Ownership and organization of enterprises.; Business communication and presentation.; elektronické knihy; electronic books